Fred Hoyle a life in science - Mitton, Simon 1946- (Cambridge University Press, 2011)
The scientific life of Fred Hoyle (1915–2001) was truly unparalleled. During his career he wrote groundbreaking scientific papers and caused bitter disputes in the scientific community with his revolutionary theories. Hoyle is best known for showing that we are all, literally, made of stardust in his paper explaining how carbon, and then all the heavier elements, were created by nuclear reactions inside stars. However, he constantly courted controversy and two years later he followed this with his 'steady state' theory of the universe. This challenged another model of the universe, which Hoyle called the 'big bang' theory. Fred Hoyle was also famous amongst the general public. He popularised his research through radio and television broadcasts and wrote best-selling novels. Written from personal accounts and interviews with Hoyle's contemporaries, this book gives valuable personal insights into Fred Hoyle and his unforgettable life
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hoyle, Fred / 1915-2001; Hoyle, Fred -- 1915-2001; Geschichte; Astronomers / Great Britain / Biography; Astronomie; Naturwissenschaften; Großbritannien; Biografie